PERAN KELOMPOK TANI DALAM MENINGKATKAN PENDAPATAN PETANI SWADAYA KELAPA SAWIT DI DESA BUKIT LINGKAR KECAMATAN BATANG CENAKU KABUPATEN INDRAGIRI HULU - Pratama, Bayu Putra; Sayamar, Eri '; Tety, Ermi ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research is to know the role of farmer group what is already run in oil palm farm at Bukit Lingkar Village Batang Cenaku District Indragiri Hulu Regency.Method which used in this research was census method. Intake of sampel conducted by purposive sampling on the farmer group which active in oil palm farm with different year growth. Data analysis used likert scale. The result showed that the role of farmer group had good enough role seen from average value of the role equal to 2,99 (Enough Role) in oil palm farm activity at Bukit Lingkar Village. This condition seen from the role of farmer group as classroom learning place with score equal to 2,91 (Enough Role), cooperation place with score equal to 3,01 (Enough Role), and production unit place with score equal to 3,04 (Enough Role). Keywords : Oil palm, The role of farmer group, independent oil palm farm.